Improving Teaching Quality and Undergraduate Students' Critical Thinking Skills through Contextual Teaching and Learning Integrated with Lesson Study in a Basic Physics Course - Atika Ulya Akmal; Leni Zahra; Aissy Putri; Ummitul Fitri (Postgraduate, University of Mataram, 2026)
This study aimed to improve teaching quality and undergraduate students' critical thinking skills through the implementation of the Contextual Teaching and Learning (CTL) model integrated with Lesson Study in a Basic Physics Concepts course. The study employed Classroom Action Research using the Lesson Study approach, which was conducted through four cycles consisting of the PLAN–DO–SEE stages. The participants were 60 first-semester students enrolled in the Elementary School Teacher Education Program at Universitas Negeri Padang. Data were collected through classroom observations, interviews, field notes, and a critical thinking assessment rubric. The data were analyzed descriptively by reducing, displaying, and interpreting the findings from each cycle. The results showed continuous improvement in both teaching practices and students' critical thinking skills throughout the implementation. Lesson Study enabled lecturers to design contextual lesson plans, facilitate collaborative learning, provide authentic learning experiences, and conduct reflective teaching practices. Students demonstrated progressive improvement in analyzing contextual problems, providing evidence-based reasoning, drawing conclusions, and communicating their ideas during classroom discussions. The final average critical thinking score reached 3.17 on a 4-point scale, indicating a good level of critical thinking. These findings suggest that integrating CTL with Lesson Study effectively enhances teaching quality while fostering students' critical thinking skills in Basic Physics learning.